Metabolic recovery after weight loss surgery is reflected in serum microRNAs. Issue 2 (28th October 2020) - Sangiao-Alvarellos, Susana; Theofilatos, Konstantinos; Barwari, Temo; Gutmann, Clemens; Takov, Kaloyan; Singh, Bhawana; Juiz-Valiña, Paula; Varela-Rodríguez, Bárbara María; Outeiriño-Blanco, Elena; Duregotti, Elisa; Zampetaki, Anna; Lunger, Lukas; et al.
Abstract : Introduction: Bariatric surgery offers the most effective treatment for obesity, ameliorating or even reverting associated metabolic disorders, such as type 2 diabetes. We sought to determine the effects of bariatric surgery on circulating microRNAs (miRNAs) that have been implicated in the metabolic cross talk between the liver and adipose tissue. Research design and methods: We measured 30 miRNAs in 155 morbidly obese patients and 47 controls and defined associations between miRNAs and metabolic parameters. Patients were followed up for 12 months after bariatric surgery. Key findings were replicated in a separate cohort of bariatric surgery patients with up to 18 months of follow-up. Results: Higher circulating levels of liver-related miRNAs, such as miR-122, miR-885-5 p or miR-192 were observed in morbidly obese patients. The levels of these miRNAs were positively correlated with body mass index, percentage fat mass, blood glucose levels and liver transaminases. Elevated levels of circulating liver-derived miRNAs were reversed to levels of non-obese controls within 3 months after bariatric surgery. In contrast, putative adipose tissue-derived miRNAs remained unchanged (miR-99b) or increased (miR-221, miR-222) after bariatric surgery, suggesting a minor contribution of white adipose tissue to circulating miRNA levels. Circulating levels of liver-derived miRNAs normalized along with the endocrine and metabolic recovery of bariatric surgery, independent of the fat percentage reduction. Conclusions: Since liver miRNAs play a crucial role in the regulation of hepatic biochemical processes, future studies are warranted to assess whether they may serve as determinants or mediators of metabolic risk in morbidly obese patients.